Advanced carrier-based modulation and design optimization for the five-level current source rectifier - Ries, Lisandra Kittel (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Elétrica, Florianópolis, 2018.